PENGARUH LATIHAN PIRAMIDA DESCENDING DENGAN IRAMA LAMBAT DAN CEPAT TERHADAP KEKUATAN, KECEPATAN, DAYA LEDAK DAN HYPERTROPY OTOT TUNGKAI - Hartoto, Setyo (Fakultas Ilmu Olahraga, Universitas Negeri Surabaya, 2017)
Related to weight training with pyramid system, in this research the researcher will focus on ascending and descending pyramid system, comparison of multiple set training with pyramid model will be done with fast and slow rhythm, rhythm comparison and pyramid drill model which will be used to know the mprovementand comparison of increased strength, speed, explosive power and hypertrophy of the leg muscles. This type of research is a quasi-experimental research, using the design of